Chronic pain is a risk factor for all-cause and cancer-specific mortality in cancer survivors: a population-based cohort study - Yeying Zhang; Yuna Guo (BMC Public Health)
Abstract Background Evidence is lacking on whether chronic pain is related to the risk of cancer mortality. This study seeks to unveil the association between chronic pain and all-cause, cancer, as well as non-cancer death in cancer patients based on the National Health and Nutrition Examination Survey (NHANES) database. Methods Cancer survivors aged at least 20 (n = 1369) from 3 NHANES (1999–2004) cycles were encompassed. Chronic pain and cancer were determined through self-report. We employed records from the National Death Index for the determination of death status and reason. All-cause, cancer, and non-cancer deaths were primary outcomes. We used time-dependent ROC curve assessment to evaluate the predictive value of chronic pain for death in cancer patients. Results Over a median 141-month follow-up (interquartile range: 61–201 months), 884 (64.57%) of 1,369 cancer sufferers died, of which 259 (18.91%) died from cancer, and 625 (45.65%) from other causes. Compared with non-chronic pain survivors, chronic pain correlated with elevated all-cause mortality (Hazard Ratio (HR), 1.40; 95% CI, 1.14–1.72, p = 0.001) and cancer death (HR, 1.75; 95% CI, 1.16–2.64, p = 0.008), primarily in patients with pain lasting 3 months or more. Chronic pain was related to higher non-cancer mortality (HR, 1.38; 95% CI, 1.04–1.82, p = 0.025), and no significant results were found in pain duration. Time-dependent ROC curves showed the area under the curve (AUC) for all-cause mortality at 1, 3, 5, 10, and 20-year survival for chronic pain of 0.71, 0.78, 0.84, 0.89, and 0.96, respectively. The AUCs for cancer mortality at 1, 3, 5, 10, and 20-year for chronic pain were 0.83, 0.87, 0.91, 0.94, and 0.95, respectively, and those for non-cancer mortality at 1, 3, 5, 10, and 20-year for chronic pain were 0.82, 0.86, 0.90, 0.91, and 0.97, respectively. Conclusion Chronic pain is associated with heightened all-cause and cancer mortality in the cancer population. Clinical staff should focus on chronic pain in this patient population.